HABITUASI MENGAJI AL-QUR’AN DALAM MENANAMKAN NILAI CINTA TANAH AIR PADA SISWA DI OB OM SCHOOL SATUN THAILAND - Desika Ismi Arifiani Fitri; Syaiful Rizal (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study investigates the role of Qur’anic recitation habituation in fostering the value of hubbul wathan (love for the homeland) among students at Ob Om School (Anuban Ob-Om), Satun, Thailand. The study was motivated by the limited research examining the development of national character through Islamic education within Muslim minority communities. A descriptive qualitative approach was employed using field research methods, including observation, interviews, and documentation. The findings reveal that the habituation of Qur’anic recitation, conducted routinely every morning through the Qiroati levels 1–5 program, not only improves students’ Qur’anic reading proficiency but also serves as a medium for internalizing the value of hubbul wathan. This value is reflected in students’ discipline, compliance with school regulations, mutual respect, and ability to interact harmoniously within a diverse social environment. The results indicate that the internalization of Qur’anic values contributes to the development of national character while maintaining the Islamic identity of students as members of a Muslim minority community. The novelty of this study lies in its exploration of the relationship between Qur’anic recitation habituation and the cultivation of hubbul wathan values among Muslim minority students in Thailand. This study confirms that Qur’anic recitation habituation functions not only as a means of strengthening religiosity but also as an effective strategy for fostering national character.